Clinical mitochondrial medicine - Chinnery, Patrick F.; Keogh, Michael (Cambridge University Press, 2018)
Mitochondrial disorders are a highly diverse group of conditions that can affect almost every major system in the human body, often mimicking common disorders. This clinical variety often results in prolonged and often dangerous, diagnostic delays. This textbook provides a practical framework, to enable rapid identification, investigation, and treatment of mitochondrial disorders across the spectrum of clinical practice. Clinically relevant and comprehensive, this textbook employs a system- and case-based approach for practitioners of all levels. It focuses on major phenotypic features, syndromes and management relevant for clinical practice, within a broad overview of the field. This interactive book supports readers with knowledge distilled from over 20 internationally recognized, mitochondrial experts.